439 Dual modes of action for anti-TIM-3 antibody MBG453 in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML): preclinical evidence for immune-mediated and anti-leukemic activity. (10th December 2020) - Sabatos-Peyton, Catherine; Longmire, Tyler; Baker, Lisa; Patel, Nidhi; Wavreille, Anne-Sophie; Verneret, Melanie; Jayaraman, Pushpa; Jiang, Xiaomo; Schwartz, Stephanie; Cremasco, Viviana; Lu, Hongbo; Qiu, Shumei; et al.
Abstract : Background: TIM-3 is expressed on leukemic stem cells (LSCs) and blasts in AML, 1 2 and TIM-3 expression on MDS blasts correlates with disease progression. 3 Functional evidence for TIM-3 in AML was established with an anti-TIM-3 antibody which inhibited engraftment and development of human AML in immuno-deficient murine hosts. 1 TIM-3 promotes an autocrine stimulatory loop via the TIM-3/Galectin-9 interaction, supporting LSC self-renewal. 4 In addition to its cell-autonomous role on LSCs/blasts, TIM-3 also has a critical role in immune system regulation, in adaptive (CD4+ and CD8+ T effector cells, regulatory T cells) and innate (macrophages, dendritic cells, NK cells) immune responses. 5 MBG453 is a high-affinity, humanized anti-TIM-3 IgG4 antibody (Ab) (stabilized hinge, S228P), which blocks the binding of TIM-3 to phosphatidylserine (PtdSer). Recent results from a multi-center, open label phase Ib dose-escalation study (NCT03066648 ) in patients with high-risk MDS and no prior hypomethylating agent therapy evaluating MBG453 in combination with decitabine demonstrated encouraging preliminary efficacy with an overall response rate of 58%, 6 and MBG453 combined with azacitidine also showed encouraging response rates. 7 Preclinical experiments were undertaken to define the mechanism of action of the hypomethylating agent and anti-TIM-3 combination. Methods: THP-1 cells (a human monocytic AML cell line) were pre-treated with decitabine and co-cultured with anti-CD3 activated healthy human donor peripheral blood mononuclear cells (PBMCs) in an Incucyte-based assay to measure cell killing. The ability of MBG453 to mediate antibody-dependent cellular phagocytosis (ADCP) was measured by determining the phagocytic uptake of an engineered TIM-3-overexpressing Raji cell line in the presence of MBG453 by phorbol 12-myristate 13-acetate (PMA)-activated THP-1 cells. Patient-derived AML xenograft studies were undertaken in immune-deficient murine hosts to evaluate the combination of decitabine and MBG453. Results: MBG453 was determined to partially block the TIM-3/Galectin-9 interaction in a plate-based MSD (Meso Scale Discovery) assay, supported by a crystal structure of human TIM-3. 8 Pre-treatment of THP-1 cells with decitabine enhanced sensitivity to immune-mediated killing in the presence of MBG453. MBG453 was determined to mediate modest ADCP, relative to controls. MBG453 did not enhance the anti-leukemic activity of decitabine in patient-derived xenograft studies in immuno-deficient hosts. Conclusions: Taken together, these results support both direct anti-leukemic effects and immune-mediated modulation by MBG453. Further studies are ongoing to determine: (1) whether MBG453 can mediate physiologically relevant ADCP of TIM-3-expressing leukemic cells; and (2) the potential of MBG453 to impact the autocrine feedback loop of TIM-3/Galectin-9. Ethics Approval: The human tissue used in these studies was under the Novartis Institutes of BioMedical Research Ethics Board IRB, Approval Number 201252867. References: Kikushige Y, Shima T, Takayanagi S, et al. TIM-3 is a promising target to selectively kill acute myeloid leukemia stem cells. Cell Stem Cell 2010;7(6):708–717. Jan M, Chao MP, Cha AC, et al. Prospective separation of normal and leukemic stem cells based on differential expression of TIM3, a human acute myeloid leukemia stem cell marker. Proc Natl Acad Sci USA 2011; 108(12): 5009–5014. Asayama T, Tamura H, Ishibashi M, et al. Functional expression of Tim-3 on blasts and clinical impact of its ligand galectin-9 in myelodysplastic syndromes. Oncotarget 2017;8(51): 88904–88917. Kikushige Y, Miyamoto T, Yuda J, et al. A TIM-3/Gal-9 autocrine stimulatory loop drives self-renewal of human myeloid leukemia stem cells and leukemic progression. Cell Stem Cell 2015; 17(3):341–352. Acharya N, Sabatos-Peyton C, Anderson AC. Tim-3 finds its place in the cancer immunotherapy landscape. J Immunother Cancer 2020; 8(1):e000911. Borate U, Esteve J, Porkka K, et al. Phase Ib Study of the Anti-TIM-3 Antibody MBG453 in combination with decitabine in patients with high-risk myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). Blood 2019;134 (Supplement_1):570. Borate U, Esteve J, Porkka K, et al. Abstract S185: Anti-TIM-3 antibody MBG453 in combination with hypomethylating agents (HMAs) in patients (pts) with high-risk myelodysplastic syndrome (HR-MDS) and acute myeloid leukemia (AML): a Phase 1 study. EHA 2020. Sabatos-Peyton C. MBG453: A high affinity, ligand-blocking anti-TIM-3 monoclonal Ab. AACR 2016.